HUBUNGAN ANTARA PELATIHAN DENGAN PRODUKTVITAS WAKTU BAKU DAN TINGKAT KEBENARAN PEKERJAAN TENAGA KERJA WANITA DI GUDANG PENGOLAH (Studi Kasus di PTPN X Kebun Ajong Gayasan Jember) - Deti Rushilani Syarif; Ati Kusmiati; Evita Soliha Hani (University of Jember, 2015)
PTPN X Ajong Gayasan Plantation Jember is a company that cultivates Down Shade Tobacco ( TBN ) in a large scale. The processing in the warehouse processor or so-called warehouse zinc is a product processing opstapel from drying warehouse to be used as cigar tobacco. This processing is done to obtain a product in the form of a product ready for sale or export of which is carried by the female labor force. This study aims to determine: (1) the correlation between work training with the level of labor productivity in the warehouse processing woman PTPN X Kebun Ajong Gayasan Jember, (2) the standard time and the amount of labor required optimal effective tobacco sorting passage in accordance with the calculation of standard time, and (3) the degree of truth employment of women workers in the warehouse sorting processing section PTPN X Kebun Ajong Gayasan Jember. The research conducted in PTPN X Ajong Gayasan Plantation Jember by purposive method. The determination of sample using Slovin Methodwith samples acquired by 42 respondents from women workers of sorting tobacco section. The data used were primary and secondary data. Data analysis tools used were: (1) Rank Spearman Method; (2) Standart Time; (3) The Level of Jobs Truth (Descriptive Method). The survey results revealed that: (1) there is a relationship between training and productivity of female workers in processing warehouses PTPN X Kebun Ajong Gayasan Jember, (2) the measurement of working time women workers sorting tobacco section PTPN X Kebun Ajong Gayasan obtained Jember cycle time (on average) is 38.968 hours/week, rating factor is 1.12, the normal time is 43.644 hours/week, the value of allowance is 29.5% and the standard time is 56.518 hours/week. While the optimal amount of labor for the efficient sorting each group average is 40 peoples/group or 20 pairs/group, and (3) The level of employment of women workers truth sorting tobacco section PTPN X Kebun Ajong Jember Gayasan is ± 95 % for the first strand of tobacco leaves, on average only 1-2 pieces of leaf tobacco that is not in accordance with the assessment indicators.Keywords : labor women, productivity, standard time, the degree of truth work, training